ATRIBUTOS FÍSICOS DO SOLO EM DIFERENTES DOSES DE VINHAÇA NO MUNICÍPIO DE NOVA ALVORADA DO SUL - Filipe Andrade de Souza , Danilo; Leandro da Silva , Maiele; Panachuki , Elói; Vieira dos Santos , Wesley; da Silva Menezes, Roniedison; Fernandes Nunes , Lethicia (ANAIS DO ENIC, 2026)
-